Eighteenth Annual Conference of the Canadian Council of Muslim Women - Sharon Hoosein (International Institute of Islamic Thought, 2002)
"Strengthening Our Voices" was a fitting topic for the most recent Canadian Council of Muslim Women (CCMW) conference held on September 13-15, 2002, at the Bank of Montreal Learning Institute, Markham, Ontario, Canada. This national organization, with chapters across Canada, was founded in 1982 when Muslim women from across Canada attended the founding conference in Winnipeg, Manitoba. This year's conference celebrated 20 years of leadership and "working towards equity, equality, and empowerment." Lila Falhman, a founding member and now 78 years old, was on hand to commemorate the event. Other founding members, current CCMW president Barbara Siddiqui, and many local chapter leaders also were present. The Bank of Montreal Learning Institute in Markham was the perfect venue, for it allowed almost 300 people to hear the keynote speakers. Tables were set up for silent auction and sales of the latest books by Farid £sack, Sadia Zaman, and Khaled Abou El Fad!. The invited keynote speaker, Beverly Amina McCloud, professor at De Paul University, (Chicago, IL) unfortunately could not attend. Graciously taking her place, however, was Sheila McDonough, professor of religion at Concordia University (Montreal, Quebec, Canada) and author of the recently released The Muslim Veil in North America: Issues and Debates (University of Toronto Press: 2002.) She engaged the audience in a lively discussion of the philosophical question "Can a Muslim Woman Think?" She logically argued that genetics are evenly distributed to offspring, so that women receive intellect from both parents; that children think as they learn; and that, in general, all homo sapiens are thinking creatures. She used several Qur'anic verses to demonstrate that God addresses women as a group separately from men and also stressed that everyone is responsible for his or her own actions on the Day of Judgment ...